Compliance: um estudo de caso sobre a estruturação do sistema de conformidade da Odebrecht S.A. - SILVA , Marcos Ricardo Cruz da (2018)
The study aims to evaluate the structuring process of the Odebrecht S.A.’s Compliance System in response to contemporary challenges faced by the company, using the case study methodology. Thar organization was chosen for its relevance, as well as for the socio-political context and complexity involved in defining its compliance framework. In order to undertake this research, it was conducted analyzes of documents and records of the company studied and individual interviews with key people in the development of the compliance system, besides a wide bibliographical revision on the structuring themes of the theoretical reference of this study. At the end of the study, it was acknowledge that: the motivators that led Odebrecht SA to the structuring of its compliance system are earlier and more comprehensive in relation to the Lava Jato operation; the structuring of corporate governance and compliance, as well as the actions of top management to sponsor / reinforce the program - have boosted the beginning of the improvement of the compliance system of Odebrecht S.A., aligned with the best Corporate Governance practices and applicable laws, without, however, reaching the targets contained in the commitments entered into by the Organization with competent authorities; with the creation of a responsible body with staff and resources that are being regularly extended, the Organization has set up a permanent structure for evaluating and improving the processes of conformity and dissemination of experiences and best practices; despite the fact that it has published a risk management methodology, Odebrecht S.A.'s risk management process is still incipient - there is still no formal risk mapping, as well as the definition of limits and the maximum acceptable risk exposure; the Organization reinforced the remodeling of the Corporate Governance and Compliance structure through the issuance of new policies, in addition to the Governance and Compliance policies; the reformulation of the company's complaints channel complemented its compliance policy in order to detect possible deviations; Odebrecht S.A. systematically extended the communication and training on the subject to all its members; the definition of an internal audit plan and the contracting of an external audit, as well as the submission of the Organization to independent monitoring, provide the necessary support for the measurement of the capacity and effectiveness of internal controls, policies and procedures, aiming to identify failures and ways of improvement of processes; and, finally, the Odebrecht S.A. compliance system is in transition from the initial stage of implementation to the consolidation stage.